The Effectiveness of a Private Human Resource Development Centre’s Outdoor Training Programme on Teamwork - Cheah, Fun Ling (2004)
The objective of this study was to determine the level of teamwork gained in clarity of goals, communication, leadership, trust, conflict management, empowerment, decision making, relationship and overall teamwork. The relationship between participants’ perception towards training content, training methodology, the instructor’s delivery, the overall perception on teamwork gained was also determined. A pre and post-test survey type questionnaire was self-administrated. There were 28 participants who had gone through Banseke’s outdoor training programme participated in pilot test. A total of 64 participants who attended the course from 25-30 October 2002 participated in this study. Teamwork assessment questionnaire was adopted and adapted from Stott & Walker (1995) to determine participants’ teamwork level. Responses were analysed using SPSS. Measures of Central Tendency, Standard Deviation and frequency were used for descriptive analysis, while Paired Sample t-test was used to determine the differences of teamwork level before and after the training programme. Pearson Correlation Coefficient was used to determine the relationship of the variables. The results revealed that participants have high perception towards training content, training methodology and the instructor’s delivery. The study also found that there was significant increment for teamwork and its elements like clarity of goals, communication, leadership, conflict management, empowerment and decision making, but not for trust and relationship. Correlation coefficient results revealed that there was no significant relationship between training content and eight elements constituted of teamwork. Training methodology has significantly low relationship with communication (r = 0.279) and leadership (r = 0.253), but no for the other six elements. Instructor’s delivery also has significantly low relationship with communication (r = 0.314) and leadership (r = 0.316), but no for the other six elements. There was no significant relationship between participants’ perception towards training content, training methodology and instructor’s delivery with teamwork. However, the overall perception of the outdoor training has significantly low relationship with teamwork (r = 0.260). The overall perception also has significantly low relationship with communication (r = 0.321) and leadership (r = 0.272). Therefore, high level of participants’ perception towards training content, training methodology and the instructor’s delivery were not necessarily the cause of teamwork gained. Banseke is an effective outdoor training programme in improving participants’ overall teamwork level.